Episodic nutrient enrichments stabilise protist coexistence in planktonic oligotrophic conditions. (28th January 2021) - Zufiaurre, Aitziber; Felip, Marisol; Giménez‐Grau, Pau; Pla‐Rabès, Sergi; Camarero, Lluís; Catalan, Jordi
Abstract: Seasonal compositional changes in plankton communities are usually considered as species replacements. Given the enormous number of individuals integrating the communities and our limited capacity to count and determine most of them, we likely observe only alternative population peaks of some of the coexisting species. The contemporary coexistence theory addresses coexistence in communities of competing species, considering relative fitness inequalities and stabilising niche differences as components of average long‐term growth rates. Here, we experimentally show that the response patterns predicted by the theory occur when varying nutrient pulses fertilise the planktonic community. We used gently self‐filling 100‐L enclosures to minimise the disturbance of the initial community and different pulse P and N additions to manipulate the apparently species‐poor epilimnetic community of an ultraoligotrophic P‐limited lake. We measured and compared the protist species growth response to gradients of P enrichment and N stoichiometric imbalance. The P and N levels used in most treatments were within the oligotrophic seasonal and inter‐annual variations of the lake and were higher in a few extreme treatments that provided mesotrophic conditions of the remote regions affected by N atmospheric contamination. We alternatively replicated all treatments using ammonium or nitrate as the N source. Most protist species, recorded in this lake across seasons in previous studies, were recovered, indicating a persistent assemblage of species that is seasonally hidden from observation. Recovery included some rare species observed only in the slush layers of the seasonal snow and ice cover. The coexistence‐stabilising mechanisms were indicated by treatment response features, such as frequency‐dependent growth, inverse relationship between fitness inequality and niche differentiation proxies, high‐rank taxonomic levels clustering across the limiting‐nutrient gradient but segregation at the species level according to the type of N supply and resting stage development depending on nutrient conditions. The response similarities between autotrophic and heterotrophic organisms indicate a network of interactions that may reinforce coexistence. Synthesis . The results indicate that many planktonic protist species in oligotrophic waters can show stable long‐term non‐equilibrium coexistence by alternately recovering from very low densities when episodic nutrient enrichments, of varying P and N amounts and composition, occur. Abstract : The experimental manipulation of a lake planktonic community using varying N and P nutrient additions to self‐filling 100‐L enclosures showed response patterns predicted by the coexistence theory. The results indicate that many protist species can exhibit stable long‐term non‐equilibrium populations by alternately recovering from very low densities when episodic nutrient enrichments, of varying amounts and composition, occur naturally.